A101. Copd Translational Studies 2020
DOI: 10.1164/ajrccm-conference.2020.201.1_meetingabstracts.a2552
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium/Olodaterol Improves Pulmonary Function and Physical Activity in Patients with Treatment-Naïve COPD

Abstract: Saga naive COPD physical activity evaluation (SCOPE) study investigator group;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Clinical trials have demonstrated that tiotropium/ olodaterol improves breathlessness 56,57 (including during exercise tests 58 ), lung hyperinflation 59 and inspiratory capacity 58,60 compared with its monocomponents, and activity-related breathlessness and breathing discomfort versus placebo 60 . This combination has also been shown to increase exercise capacity during walking and cycling tests 60,61 versus placebo and improve physical activity in treatment-naive patients, as indicated by reductions in breathlessness and in the amount of time spent in a sedentary position 59,[62][63][64][65] . Notably, in a multicentre, multinational clinical trial, improvements from baseline in exercise endurance time for both cycling (19%) and walking (20%) were observed in patients with COPD following 6 weeks of treatment with tiotropium/olodaterol 66 .…”
Section: The Role Of Bronchodilators On Physical Activity In Copd: Re...mentioning
confidence: 99%
“…Clinical trials have demonstrated that tiotropium/ olodaterol improves breathlessness 56,57 (including during exercise tests 58 ), lung hyperinflation 59 and inspiratory capacity 58,60 compared with its monocomponents, and activity-related breathlessness and breathing discomfort versus placebo 60 . This combination has also been shown to increase exercise capacity during walking and cycling tests 60,61 versus placebo and improve physical activity in treatment-naive patients, as indicated by reductions in breathlessness and in the amount of time spent in a sedentary position 59,[62][63][64][65] . Notably, in a multicentre, multinational clinical trial, improvements from baseline in exercise endurance time for both cycling (19%) and walking (20%) were observed in patients with COPD following 6 weeks of treatment with tiotropium/olodaterol 66 .…”
Section: The Role Of Bronchodilators On Physical Activity In Copd: Re...mentioning
confidence: 99%